2011
DOI: 10.1007/s10755-011-9201-0
|View full text |Cite
|
Sign up to set email alerts
|

The Adult Student and Course Satisfaction: What Matters Most?

Abstract: Student satisfaction with a course is important because it can contribute to student retention, and it can also be used as one way to assess faculty effectiveness. This investigative work suggests that course satisfaction among non-traditional, adult students seeking business degrees is positively influenced by giving attention to four specific service-based factors. Based on feedback from 1,725 such students and 214 instructors at five institutions of higher education, a service-based model of course satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 19 publications
(21 reference statements)
1
19
1
7
Order By: Relevance
“…Another interesting finding was that in Mauritius, the academic credentials of the instructor did not emerge as a factor affecting students’ satisfaction. This is contrary to findings by Howell and Buck (2012) who found that instructor subject matter competency was one of the four main criteria impacting student satisfaction. This may be due to a combination of reasons: students took for granted that instructors appointed by the university would be qualified; the difference between traditional older students and those of millennials; or that the students relied more on course materials to learn autonomously.…”
Section: Resultscontrasting
confidence: 99%
“…Another interesting finding was that in Mauritius, the academic credentials of the instructor did not emerge as a factor affecting students’ satisfaction. This is contrary to findings by Howell and Buck (2012) who found that instructor subject matter competency was one of the four main criteria impacting student satisfaction. This may be due to a combination of reasons: students took for granted that instructors appointed by the university would be qualified; the difference between traditional older students and those of millennials; or that the students relied more on course materials to learn autonomously.…”
Section: Resultscontrasting
confidence: 99%
“…The significance of student satisfaction is widely reported on in literature [29][30][31]. Satisfied students will among other things make positive recommendations to other students [32], continue their study until graduation [33], provide word of mouth marketing for higher educational institutions [34] and have a general positive influence on the educational process.…”
Section: Example Of a Student Comment (Unedited)mentioning
confidence: 99%
“…Los estudios de satisfacción de los estudiantes universitarios son importantes porque van a incidir directamente en la disminución de las tasas de fracaso y abandono y porque, además, va a proporcionar importante información para la mejora de la actividad docente (Howell y Buck, 2012). En estudios que se han realizado en el contexto norteamericano, como por ejemplo el de Tessema et al (2012), se concluye que los principales elementos y dimensiones que infl uyen en la satisfacción de los estudiantes universitarios son, además de la calidad de la docencia en un sentido estricto, la atención y la orientación a los estudiantes y la individualización de la enseñanza; todas estas consideraciones nos hacen retomar el valor de la tutoría universitaria, siendo una de sus grandes aportaciones, como señalan Álvarez-Pérez y González-Afonso (2010), el incremento de la satisfacción de los estudiantes (agentes prioritarios en este escenario).…”
Section: Introductionunclassified